2009
DOI: 10.2807/ese.14.28.19271-en
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-based and monoclonal antibody typing of Legionella pneumophila isolated from patients in Portugal during 1987-2008

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…As other studies have shown [20,21,29,30,31], the presented confirms that the routine analysis of environmental strains may be an important strategy for preventing outbreaks of legionellosis, in association with clinical surveillance data.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As other studies have shown [20,21,29,30,31], the presented confirms that the routine analysis of environmental strains may be an important strategy for preventing outbreaks of legionellosis, in association with clinical surveillance data.…”
Section: Discussionsupporting
confidence: 62%
“…The results were compared with those in the EWGLI database [25] which collates details of L. pneumophila strains, serogroups, monoclonal antibody subgroups and SBT profiles from all over the world [8,18,19,20,21], and with the authors'previous data [22,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…ST1 (1, 4, 3, 1, 1, 1) is distributed broadly throughout the world (3,8,20,44) and was the predominant profile in this study. However, the profile of ST-K1 (7,12,17,3,35,11) was not detected in the HPA/EWGLI SBT database or in any other studies.…”
Section: Discussionmentioning
confidence: 96%
“…According to the studies of the distribution of Lp1 STs in different regions of the world, it appears that the most prevalent ST among clinical and environmental populations of Lp1 is either ST1 (8,(27)(28)(29)(30)(31)(32) or an ST that is confined to a specific geographic region (33)(34)(35). For example, in Belgium and the United Kingdom, the most frequently detected ST among clinical isolates was ST47 (9,35).…”
Section: Discussionmentioning
confidence: 99%